The Mother's picture alphabet - Anelay, Henry, 1817-1883 (New York : Dover Publications, 1974)
Rhymed verses introduce the letters of the alphabet.
Poems.
Reprint of the 1862 ed. published by S. W. Partridge at the Office of the Children's Friend, London.
Keywords: Alphabet